Pengetahuan dan Efikasi Diri terhadap Pengendalian Nyeri pada Pasien Kanker Serviks - Reni Aniarti (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Cervical cancer is a serious health problem related to genecological cancer in women. Long-term, ongoing cervical cancer therapy and treatment can cause treatment side effects and physical discomforts such as pain, which can reduce the patient's quality of life. Knowledge and self-efficacy towards cervical cancer pain controlling are vital to improve the quality of life of cervical cancer patients. Methods: This study aims to determine the description of knowledge and self-efficacy towards pain controlling in cervical cancer patients undergoing cancer treatment. This descriptive study with a cross sectional design of 57 subjects through a consecutive sampling approach. Univariate analysis was utilized to provide information on each variable studied and presented in the form of descriptive data. Results: Of the 57 respondents, cervical cancer patients had poor knowledge and low self-efficacy as many as 17 respondents (51.52%) and respondents who had good knowledge and high self-efficacy as many as 10 respondents (41.67%). Conclusion: Knowledge and self-efficacy are important as a form of self-confidence and individual confidence in controlling pain in cervical cancer patients